PEMANFAATAN MEDIA TEKNOLOGI INFORMASI DAN KOMUNIKASI TUTORIAL SEBAGAI SUPLEMEN EKSPERIMEN - Junia Yurika; Agus Suyatna; Viyanti Viyanti (Jurnal Pembelajaran Fisika, 2014)
The goals of this research were to determine the differences in cognitive learning outcomes, describe the Science Process Skills (SPS), the character, the activities and students’ attitudes toward the use of media ICT tutorial as a supplement experiment in the learning measuring instruments. The research design used One-Shot Case Study. The sample of this research was class VIID of SMPN 2 Way Tenong randomly. The data was analyzed by using pair sample t-test. The researcher concludes by the use of media ICT tutorial as supplement experiment that the differences in cognitive learning outcomes can bring up SPS, to build character, to increase the activity of students and to foster positive attitudes of students toward the use of ICT media tutorial as a supplement experiment in the learning measuring instruments.Tujuan penelitian ini untuk mengetahui hasil belajar ranah kognitif, mendeskripsikan Keterampilan Proses Sains (KPS), karakter, aktivitas dan sikap siswa terhadap pemanfaatan media TIK tutorial sebagai suplemen eksperimen terhadap peningkatan. Desain penelitian menggunakan One-Shot Case Study. Sampel penelitian ini kelas VIID SMPN 2 Way Tenong menggunakan teknik random. Kesimpulan penelitian setelah pemanfaatan media TIK tutorial sebagai suplemen eksperimen terdapat peningkatan hasil belajar ranah kognitif, memunculkan KPS, membentuk karakter, meningkatkan aktivitas siswa serta menumbuhkan sikap positif siswa terhadap pemanfaatan media TIK tutorial sebagai suplemen eksperimen dalam pembelajaran alat ukur.Kata kunci: media TIK tutorial, suplemen eksperimen, keterampilan proses sains, karakter siswa, aktivitas siswa.